2013
DOI: 10.1124/dmd.112.050260
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Efflux Transporters Involved in Distribution and Disposition of Apixaban

Abstract: The studies reported here were conducted to investigate the transport characteristics of apixaban (1-(4-methoxyphenyl)-7-oxo-6-(4-(2-oxopiperidin-1-yl)phenyl)-4,5,6,7-tetrahydro-1H-pyrazolo [3,4-c]pyridine-3-carboxamide) and to understand the impact of transporters on apixaban distribution and disposition. In human permeability glycoprotein (P-gp)-and breast cancer resistance protein (BCRP)-cDNA-transfected cell monolayers as well as Caco-2 cell monolayers, the apparent efflux ratio of basolateral-to-apical (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 43 publications
6
101
0
4
Order By: Relevance
“…20,21 All of the DOACs are substrates for P-glycoprotein and potent inhibitors or inducers of P-glycoprotein can increase or decrease the plasma concentrations of the DOACs, respectively. [22][23][24][25] The DOACs are cleared through renal and extrarenal pathways. The extent of renal clearance varies and of the absorbed unchanged drug, the kidneys are responsible for clearance of 80% of dabigatran, 50% of edoxaban, 33% of rivaroxaban, and 27% of apixaban.…”
Section: Pharmacology Of Doacsmentioning
confidence: 99%
“…20,21 All of the DOACs are substrates for P-glycoprotein and potent inhibitors or inducers of P-glycoprotein can increase or decrease the plasma concentrations of the DOACs, respectively. [22][23][24][25] The DOACs are cleared through renal and extrarenal pathways. The extent of renal clearance varies and of the absorbed unchanged drug, the kidneys are responsible for clearance of 80% of dabigatran, 50% of edoxaban, 33% of rivaroxaban, and 27% of apixaban.…”
Section: Pharmacology Of Doacsmentioning
confidence: 99%
“…Previous data with apixaban demonstrated that the drug was a substrate for efflux transporters P-gp and BCRP (Zhang et al, 2013). In this study, we investigated the impacts of intestinal excretion (IE) and enteroenteric recirculation (EER) as well as renal tubule recirculation (RTR) (Fig.…”
mentioning
confidence: 99%
“…Совместное введение напроксена не оказывало влияния на фармакокинетику апиксабана: 90% доверительное среднее геометрическое соотношение для C max апик-сабана с напроксеном или без напроксена находилось в интервале эквивалентности (125 %). Было установ-лено, что отсутствовала разница между Т max или Т 1/2 апиксабана с напроксеном и без него, механизм этого взаимодействия стал результатом лучшей биодоступно-сти апиксабана с напроксеном или без [45]. Показатели ингибитора Ха фактора свертывания крови и МНО были одинаковыми при использовании апиксабана [78,79].…”
Section: N¹ 5(83) 2016unclassified